Dekonstruksi Superioritas Kulit Putih: Nilai Luhur Aborigin dalam The Track to Bralgu Karya Wongar - Didimus Estanto Turuk Estanto Turuk (Balai Bahasa Provinsi Riau, 2019)
This research aims to rewrite the paradigm of a superior invader and the inferior colonized using Derridian deconstruction in The Track to Bralgu, a novel by Streten Bozig Wongar. It examines the depictions of the Aborigine to identify the superiority paradigm that is represented on the characters’ description and reveals how the depiction of the characters in the story brings the idea of the superiority of the colonized toward the colonizer by deconstructing the White’s paradigm. A descriptive qualitative method is a method used and a postcolonial approach is applied to conduct the research. The results of the study show that (1) the qualities of the Aborigine people which show themselves not being inferior are tracking and living in the bush, taking care of human being, transforming from human form into an animal form, and honoring the corpse; (2) the qualities of the Aborigine which deconstruct White’s constructed paradigm are skillfulness, humanity, and faith; and (3) the Aborigine people have no intentions to be better than the White people, they just live the way they believe. By living the life the way they believe, it is proven that the Aborigine people do gain the paradigm of superiority in the period of colonization.